A multi-color persistent luminescent phosphor β-NaYF4:RE3+ (RE = Sm, Tb, Dy, Pr) for dynamic anti-counterfeiting. Issue 18 (13th April 2022) - Wang, Bohan; Wang, Zhihao; Mao, Peng; Wang, Yu
Abstract : A dynamic anti-counterfeiting pattern was successfully designed by using the excellent luminescence characteristics of long afterglow materials under X-ray excitation. Abstract : Conventional luminescent materials generally exhibit uni-color and transient emission under UV excitation, which makes them mediocre in the field of anti-counterfeiting. The high-level anti-counterfeiting techniques are always becoming more complicated and in need of multi-color and persistent luminescent materials. Herein, we report a series of β-NaYF4 :RE 3+ (RE = Sm, Tb, Dy, Pr) persistent luminescent phosphors with multi-color emitting and ultra-long persistent luminescence under the irradiation of X-rays. The effects of doping concentrations of RE 3+ on the size, morphology, radioluminescence and afterglow performance of the products are investigated in detail. Hexagonal structured rod-like β-NaYF4 :Tb 3+ crystals show super strong X-ray response and the afterglow signal lasts for up to seven days after X-rays are turned off. Upon X-rays irradiation, some of the F − ions are expected to escape from the crystal lattice by elastic collisions, leading to the generation of Frenkel defects: the F vacancies and interstitials, which capture electrons and release them slowly to achieve different afterglow emission times. Taking advantages of the extraordinary radioluminescence performance of the β-NaYF4 :RE 3+ persistent luminescent phosphors, the dynamic anti-counterfeiting patterns that containing rich time-resolved information were successfully designed.